Determinants of Environmental Sanitation in the City of Tshwane, South Africa - Worku, Yohannes; Muchie, Mammo (Transactions on Engineering and Computing Sciences, 2018)
The purpose of the study was to identify and quantify key predictors of satisfactory municipal services on municipal waste management in the City of Tshwane, South Africa. The expected and perceived quality of waste management services were analysed by using SERVQUAL analysis. The study found that the perception and expectation of respondents on the quality of sanitary services provided to them were significantly influenced by the degree of motivation of employees of the City of Tshwane at work, the ability of employees of the City of Tshwane to treat all customers with respect, the ability of employees of the City of Tshwane to provide adequate answers promptly to queries raised by customers, and the degree to which employees of the City of Tshwane were skilled on technical issues, in a decreasing order of strength.